A method to calculate and measure losses and efficiency in DC-DC converters - vesali, mahmood (JAREE (Journal on Advanced Research in Electrical Engineering), 2023)
In this paper, training on how to calculate and measure losses in power converters is presented. In the power converters all elements have losses due to circuit condition, therefore in order to calculate the losses in the elements, all conditions are considered, so the accuracy of the calculations are high. All relationships and formulas for calculating losses are presented, so the different ways of calculating losses are clear in this paper. All basic converters in this paper are studied in term of losses, so this paper is a good reference for calculating losses in DC-DC converters. In converters with soft switching, elements are added that also have losses in the converter, which the method of obtaining losses of these elements is also taught. Finally, methods for obtaining losses in simulation and experimental prototypes are given that prove the methods and theoretical formulas.